Dyspareunia caused by a vaginal adhesion band following a transvaginal mesh repair - Cheng-Yu Long; Ming-Ping Wu (Wolters Kluwer Medknow Publications, 2013)
Surgery with synthetic mesh or graft materials has become increasingly popular over the past decade due to the excellent short-term success rate. However, concern about mesh-related complications still exists. Here we report a case experiencing sexual pain after a transvaginal mesh repair with a total Prolift procedure. Also, her husband experienced painful intercourses due to a vertical adhesion band between the anterior and posterior vaginal wall. Under local anesthesia, the adhesion band was dissected. She restarted her sexual life 3 weeks after the procedure without any further complaint. A postoperative vaginal adhesion band formation may occur during the healing process, which may cause postoperative sexual dysfunction. This rare complication may aid in preoperative counseling about the potential adverse events on postoperative sexual function.